Empire and Power in the Reign of Süleyman : Narrating the Sixteenth-Century Ottoman World - Şahin, Kaya, 1974- (Cambridge : Cambridge University Press, 2013)
"On a torrid August day in 2009, I visited Celalzade Mustafa's final resting place in Istanbul's Eyüp district, in a neighborhood called Nisanca. The chancellor (nisanci) is buried in the cemetery adjoining the small mosque built for him by Sinan, the chief imperial architect. His brother Salih, a teacher, judge and religious scholar, is buried nearby, but the sepulchres of poets who received plots from this patron of poetry have disappeared. The mosque, adorned with glazed tiles, has changed significantly since the mid-sixteenth century. It was damaged in a fire in 1729, and was rebuilt following a more devastating fire in 1780. The mansion where Mustafa composed his works, welcomed fellow literati, and provided advice to young and aspiring secretaries is long gone, probably destroyed in the fire of 1780, if not before"--Provided by publisher.
Introduction: Revisiting Celalzade Mustafa -- Part One. Celalzade Mustafa and the New Ottoman Empire in Early Modern Eurasia -- The Formative Years (1490-1523) -- The Secretary's Progress (1523-1534) -- The Empire and Its Chancellor (1534-1553) -- Towards the End (1553-1567) -- Part Two. Narrating, Imagining, and Managing the Empire -- Narrating the Empire : History-Writing between Imperial Advocacy and Personal Testimony -- Imagining the Empire : The Sultan, the Realm, the Enemies -- Managing the Empire : Institutionalization and Bureaucratic Consciousness -- Conclusion: Beyond Ottoman and European exceptionalism: empire and power in sixteenth-century Eurasia.
Includes bibliographical references and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Mustafa Çelebi Celâlzade, -- -1567.; Mustafa Çelebi Celâlzade, -- -1567 -- Political and social views; Mustafa Çelebi Celâlzade, -- -1567 -- Criticism and interpretation; Mustafa Çelebi Celâlzade, -- -1567; Celālzāde Muṣṭafā Čelebī -- 1490-1567; Turkey -- Officials and employees -- Biography; Historians -- Turkey -- Biography; Turkey -- History -- Süleyman I, 1520-1566 -- Historiography; Historiography -- Turkey -- History -- 16th century; Turkey -- History -- Süleyman I, 1520-1566.; Imperialism -- History -- 16th century; Power (Social sciences) -- Turkey -- History -- 16th century; Asie Mineure -- Fonctionnaires -- Biographies; Empire ottoman -- Histoire -- 1520-1566 (Soliman Ier) -- Historiographie; Empire ottoman -- Histoire -- 1520-1566 (Soliman Ier); Impérialisme -- Histoire -- 16e siècle.; HISTORY -- Middle East -- General; BIOGRAPHY & AUTOBIOGRAPHY -- Historical; Employees; Historians; Historiography; Imperialism; Political and social views; Power (Social sciences); Turkey; Verwaltung; Osmanisches Reich; 1500-1599; Biographies; Criticism, interpretation, etc; History